Short-Run Objectives of Monetary Policy - Noyes, Guy E. (The Review of Economics and Statistics, 1963)
F what I have seen of the work of the Commission on Money and Credit, one thing stands out.It is a part of one question addressed by one task force to the Federal Reserve Board, and it reads as follows: "Given the customary credit control instruments and the ultimate objectives of price stability, highlevel employment, and economic growthhow is monetary policy formulated in the short run?For instance, what sort of factors are weighed in determining current policy, what guides are utilized and what are the immediate objectives of policy?"The merits of the Board's reply, the many contributed papers, the Commission's Report, and recent monetary policy itself, are all certainly debatablebut I submit, if you will pardon the use of strong language, that this is a damned good question.It asks, politely but firmly, that we omit the usual garbage about opposition to sin and advocacy of motherhood, and just say what it is we are trying to increase, decrease, or hold still.The Board's reply ran to some 35 doublespaced pages.The burden of drafting was carried by my colleague, Woody Thomas,